First Isaiah: a commentary - Roberts, Jimmy J. M. (Hermeneia--a critical and historical commentary on the Bible, 2015)
1:1. Heading -- 1:2-20. The covenant lawsuit -- 1.21-28. The city of God : renewal of a symbol -- 1:29-31. The sacred groves -- 2:1. A second heading -- 2:2-22. The future exaltation of Zion : a warning against the North -- 3:1-15. Judgment on Judah -- 3:16-4:1. The haughty women of Zion -- 4:2-6. The purified Jerusalem -- 5:1-7. The song of the vineyard -- 5:8-24. The Hoy-Oracles -- 10:1-4; 5:25-30. Two misplaced pericopes -- 6:1-9:7 (9:6 Heb.). A collection of Isaiah's memoirs -- 9:7-20 (Eng. 9:8-21) + 5:25-30. Judgment on Israel -- 10:5-34. Judgment on Assyria, God's arrogant tool -- 11:1-10. The shoot of Jesse -- 11:11-16. The reunification of Judah and Ephraim -- 12:1-6. A hymn of praise for salvation -- 13:1-22. Yahweh summons the Medes to punish Babylon -- 14:1-4. Introduction to the Taunt song -- 14:4b-21. The Taunt song -- 14:22-23. An exilic addition -- 14:24-27. God's plan for Assyria -- 14:8-32. The rod that smote Philistia -- 15-16. An oracle over Moab -- 17.1-14. Oracles against Damascus and Ephraim -- 18.1-7. An oracle against Nubia -- 19.1-25. An extended oracleor oracles against Egypt -- 20.1-6. The Ashdod affair -- 21.1-10, 11-12, 13-17. Three disputed oracles -- 22:1-14. The collapse of the Babylonian front and the sin of Jerusalem's elite -- 22:15-25. Shebna and Eliakim -- 23:1-18. The oracle against Tyre -- 24-27. The little Isaiah apocalypse -- 18:1-6. An early oracle against the North -- 28:7-22. The extension of that oracle against the Judean leaders -- 28:23-29. The parable of the farmer -- 29:1-8. Yahweh's punishment and deliverance of Jerusalem -- 29:9-14. Willful blindness and God's marvelous work -- 29:15-16. The folly of Judah's counselors -- 29:17-24. A reworked promise to the North -- 30:1-5. Against God's rebellious children who make a treaty with Egypt -- 30:6-7. Oracle about the beasts of the Negeb -- 30:8-17. Writing down the prophecy as a witness for the future -- 30:18-26. Yahweh's promise of a better future for Zioin -- 30:27-33. Yahweh comes in fiery judgment -- 31:1-9. A composite oracle against reliance on Egypt -- 32:1-8. The transformed society of the rulers and ruled in the age of salvation -- 32:9-29. Against carefree women adn the judgment and deliverance to come -- 33:1-24. An Isaianic elaboration of the Zion tradition -- 34-35 -- 34:1-17. Oracle against Edom -- 35:1-10. The return of God's people to Zion -- 36-39. Stories about Hezekiah and Isaiah -- 36:1-37:8. Sennacherib's campaign against Hezekiah -- 37:9-38. Sennacherib's letter to Hezekiah and Isaiah's response -- 38:1-8, 21. Hezekiah's illness and cure -- 38:9-20. The Psalm of Hezekiah -- 39:1-8. Merodach-Baladan's embassy to Hezekiah.